TEACHING WRITING IN ENGLISH AS A FOREIGN LANGUAGE - Purna Wijaya, I Made (Lingual: Journal of Language and Culture, 2015)
This article aims at describing about teaching writing in English as a foreign Language. The reasons for teaching writing to students of English as a Foreign language include reinforcement, language development, learning style and the most importantly, writing as skill in its own right. Like many other aspects of English language teaching, the type of writing that students should do, will depend on their age, interest and level.Â Â These include writing post cards, letters of various kinds, filling in forms such as job applications, writing narrative compositions, report, newspaper and magazine article. The result showed that the studentsâ success of writing such matters absolutely depend on their motivations